A Limited Area Modeling Capability for the Finite‐Volume Cubed‐Sphere (FV3) Dynamical Core and Comparison With a Global Two‐Way Nest. (19th June 2021) - Black, T. L.; Abeles, J. A.; Blake, B. T.; Jovic, D.; Rogers, E.; Zhang, X.; Aligo, E. A.; Dawson, L. C.; Lin, Y.; Strobach, E.; Shafran, P. C.; Carley, J. R.
Abstract: The development of a limited area model (LAM) capability for the nonhydrostatic Finite‐Volume Cubed‐Sphere (FV3) dynamical core is described and compared with a globally nested approach featuring two‐way feedback. Comparisons of the computational performance of the LAM relative to the two‐way nest reveal that the LAM configuration exhibits considerable improvement in efficiency. High‐resolution (i.e., 3‐km) LAM and nest configuration forecasts covering a 1‐month period show statistically comparable results for most parameters. Forecast differences between the two configurations primarily arise in the upper air temperature and height fields, which show a statistically significant increase in the magnitude of negative biases in geopotential height and upper‐air temperature using the LAM configuration relative to the nest at forecast lead times >24‐h. Precipitation forecasts over the full 60‐h forecast period are also evaluated and depict no statistically significant differences between the two configurations, with the nest configuration exhibiting slightly improved scores. Overall results suggest that while the FV3 LAM approach can introduce degradations into the forecast relative to the two‐way interactive nest at lead times >24‐h, these errors are generally small in magnitude and are accompanied by considerable improvement in computational efficiency. Plain Language Summary: In this study, we describe and evaluate a new limited area model (LAM) capability for the Finite‐Volume Cubed‐Sphere dynamical core. This capability provides a way to run the dynamical core over any region without the need for simultaneous integration of a global model counterpart, thus saving considerable computational resources. However, this framework is susceptible to errors from lateral boundaries, which are provided by an external model at a coarse temporal frequency compared to a global model employing a nest with two‐way feedback. Short range forecasts at 3‐km grid spacing over the contiguous United States show generally similar performance between the limited area and nest configurations for a month‐long period in 2019, with the nest showing slightly better forecast scores near the end of the studied forecast length of 60 h. These results suggest that use of the LAM performs similarly to the more sophisticated, and computationally expensive, two‐way nest configuration for convection‐allowing, short range forecasts to 60 h. Key Points: A limited area modeling capability has been developed for the Finite‐Volume Cubed‐Sphere dynamical core This capability was evaluated for a month‐long period against a similarly configured two‐way nest driven by a global model The limited area model is statistically comparable to the two‐way nest for the first 24 h, with minor degradation by 48–60 h